Relationship Between Length and Weight and Habitat Conditions of Several Fish Species in Tondano Lake, Minahasa, North Sulawesi - Rosenta Sipayung; Helen Joan Lawalata; Iriani Setyawati; Livana Dethris Rawung; Rievo Handry Djarang (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2023)
The snake-head gudgeon or payangka fish (Ophieleotris aporos), tilapia fish or mujair (Oreochromis mossambicus), and marble goby or betutu fish (Oxyeleotris marmorata) are economically important fish in Lake Tondano. However, numerous community activities can disrupt aquatic biodiversity, declining Lake Tondano environmental conditions, and other factors. This study aimed to determine the relationship between length and weight and the habitat conditions of Ophieleotris aporos, Oreochromis mossambicus, and Oxyeleotris marmorata. The method used in this study was purposive sampling with research stations located at Remboken (station 1), Kakas (station 2), and Tondano Estuary (station 3). Sampling was carried out 5 times in every 10 days. The weight and length of the fishes caught in Lake Tondano were 2-60 g and 1-8 cm (Ophieleotris aporos); 9-180 g and 6-25.5 cm (Oreochromis mossambicus); and 16-30 g and 2.6-26.5 cm (Oxyeletotris marmorata), all of them have an allometric growth pattern. Oreochromis mossambicus is the most commonly caught fish in all research stations. The research station with the best level of water fertility is Remboken Station. The habitat characteristic of Lake Tondano was 25-290C of water temperature; brightness of 1.34-2.66 m; depth of 4.23-11.8 m; pH of 6.7-7.8; and dissolved oxygen of 2.27-6.31 mg/L, which still supports the well-being of the fish.